The league. The complete season 6 [videorecording (DVD)] - Schaffer, Jeff; Marcus Schaffer, Jackie; Duplass, Mark; Kroll, Nick; Scheer, Paul, 1976-; Rannazzisi, Stephen, 1978-; Aselton, Katie, 1978- (Twentieth Century Fox Home Entertainment, 2015)
TV's funniest fantasy football fanatics return for Season Six and the stakes have never been higher, because this year they₂re playing for way more than The Shiva. Things kick off on an up note when a league member drops dead, forcing the gang to draft at his funeral. It's downhill from there, as Ruxin "juices" up his son₂s play on the little league field, Taco starts a charity and things get awkward between Kevin and his urologist.